Diversion of Corruption Eradication Commission of The Republic of Indonesia Employees To State Civil Apparatus - Bima, Muhammad Rinaldy (SASI, 2023)
Introduction: This article analyzes the regulation legislation related to the transition of employee Commission Eradication Corruption (CEC) became Apparatus Civil State (ACS). Based on the mandate of the CEC Law, it assesses CEC employees through National Insight Test (NIT) to measure integrity, neutrality, and radicalism, on March 18 until 09 April 2021 against thousand three hundred and fifty-one CEC employees. However, the implementation of NIT reaped the pros and cons.Purposes of the Research: This study aims to analyze the validity test outlook nationality in the transfer of employee status Commission Eradication Corruption Becomes Apparatus Civil State and employee status Commission Eradication Corruption that does not pass the test outlook nationality based on regulation legislation.Methods of the Research: The method used in the study is method research law normative with analysis data descriptive-prescriptive, using approach statutes and conceptual approach.Results of the Research: The results of the research show the validity of NIT already based on Constitutional Court Decision Number: 34/PUU-XIX/2021, Law Number 19 of 2019, Law Number 5 of 2014, Government Regulation No. 41 of 2021, Supreme Court Decision Number 2 P/HUM/2020, Regulation of the Minister of Administrative Reform and Bureaucratic Reform of the Republic of Indonesia Number 61 of 2018, and CEC Regulation Number 1 of 2021. The status of CEC employees who do not pass the NIT is terminated based on CEC Decree Number 1354 of 2021. The study concludes that it results from NIT already corresponding Supreme Court decision Number 34/PUU-XIX/2021, and Law Number 19 of 2019 concerning the CEC. The Recommendation for this study is National Insight Test should be more transparent, consider the Constitutional Court's decision, and direct the president.